2002
DOI: 10.1097/00004836-200204000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Permeation and Gastrointestinal Disease

Abstract: The gastrointestinal tract constitutes one of the largest sites of exposure to the outside environment. The function of the gastrointestinal tract in monitoring and sealing the host interior from intruders is called the gut barrier. A variety of specific and nonspecific mechanisms are in operation to establish the host barrier; these include luminal mechanisms and digestive enzymes, the epithelial cells together with tight junctions in between them, and the gut immune system. Disruptions in the gut barrier fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
184
1
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(193 citation statements)
references
References 95 publications
1
184
1
7
Order By: Relevance
“…Although the link between activation of the GI immune system and pancreatic beta cell destruction is incompletely understood, current knowledge suggests that antigens are presented to the gut-associated lymphoid tissue (GALT) through the paracellular pathway (6). Lymphocytes are known to circulate between GALT, lymph nodes, and other tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the link between activation of the GI immune system and pancreatic beta cell destruction is incompletely understood, current knowledge suggests that antigens are presented to the gut-associated lymphoid tissue (GALT) through the paracellular pathway (6). Lymphocytes are known to circulate between GALT, lymph nodes, and other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The specific cells involved in this immune response include antigen-presenting cells, T and natural T killer lymphocytes (NK), B lymphocytes, and plasma cells (5). These cells lie in close proximity to the intestinal epithelial barrier and facilitate immune responsiveness, especially in the presence of elevated intestinal epithelial permeability (6). Recent reports suggest that quantitative and͞or qualitative deficiencies in a subset of NK cells occur in several autoimmune diseases, including type 1 diabetes (T1D) (7) and celiac disease (CD) (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…'Leaky gut' is the name given for this increase in intestinal permeability and is commonly seen in patients presenting with inflammatory bowel disease, 5 food allergies and intolerances 6 and celiac sprue. 7 Intestinal permeability may be the main cause of sensitivity to particular types of food. In a study authored by Ventura, a statistically significant difference was found in intestinal permeability in subjects with food allergy or hypersensitivity compared to controls, and the results indicated that the worse the permeability, the more serious the clinical symptoms.…”
Section: From Function To Dysfunctionmentioning
confidence: 99%
“…Translocation of enteric bacteria is the most important cause of infection in the pancreatic tissue, and subsequent events such as sepsis and related complications [2,3] . Currently, several treatment options have been proposed for the septic complications of AP.…”
Section: Introductionmentioning
confidence: 99%